Diversifikasi Produk Udang Tambak: Strategi Cerdas Peningkatan Gizi dengan Protein Hewani Pada Anak SDN 013 Padang Lampe Kecamatan Ma’Rang Kabupaten Pangkep - Nurgahayu Nurgahayu; Linda Hardianti Saputri (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
Pangkep Regency is a district in South Sulawesi with quite well-known shrimp farming products. The animal protein content in shrimp is very good for children's growth and development and intelligence. Based on an initial survey conducted at the partner location of SDN 013 Padang Lampe, Ma'rang District, Pangkep Regency, it was found that many children did not bring their own supplies from home, they only relied on snacks available around the school. The aim of the service is to increase students' knowledge (i) regarding the dangers of consuming snacks carelessly, the benefits of consuming shrimp for growth and development and brain intelligence. improve students' skills (i) making shrimp meatballs which can be used as healthy and practical school supplies.The activity method is in the form of an educational program, as well as training in making meatballs. UMI FKM lecturers have carried out community service activities funded by the UMI Community Service Institute at SDN 013 Padanglampe, Ma'Rang District, Pangkep Regency on September 11 2024. This activity was attended by class 6 and accompanied by the class teacher. After providing education, there was an increase in students' knowledge (i) regarding the dangers of consuming snacks carelessly and the benefits of consuming shrimp for growth and development and brain intelligence by 86.7%. And student (i) was very enthusiastic about making shrimp meatballs, and really liked the taste of shrimp meatballs.